2014
DOI: 10.3892/etm.2014.1690
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ligustilide on Ang II-induced hypertrophy in cardiomyocytes and the potential mechanisms

Abstract: The aim of the present study was to investigate the effect of ligustilide (LIG) on angiotensin II (Ang II)-induced hypertrophy in neonatal rat myocardial cells and the expression levels of p53, Bcl-2 and Bax. Myocardial cells were isolated and purified from the ventricles of neonate Sprague-Dawley rats (age, 1–3 days) using a differential adhesion method. The cells were then were stimulated by Ang II and LIG for 1–3 days, following which the cell surface area, intracellular protein concentration, rate of apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Similar results were reported in other studies. 6,13,35 Stigmasterol displayed potent apoptosis inductive effects by up-regulation of p53 and bax and downregulation of bcl-2 respectively in HepG2 cells 12 and the U937 cell line, 36 which is consistent with our results obtained from Ang II-induced A7r5 cells.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar results were reported in other studies. 6,13,35 Stigmasterol displayed potent apoptosis inductive effects by up-regulation of p53 and bax and downregulation of bcl-2 respectively in HepG2 cells 12 and the U937 cell line, 36 which is consistent with our results obtained from Ang II-induced A7r5 cells.…”
Section: Discussionsupporting
confidence: 86%
“…5 Recently, it was substantiated in vitro and in vivo that Ang II-mediated cardiomyocyte proliferation is associated with the P53-dependent apoptotic signaling pathway. [6][7][8] Phytosterols are well-known chemicals in plants with structural similarity to cholesterol. Previous studies had reported that phytosterols could diminish cholesterol, modulate immune systems, reduce risks of coronary and cardiovascular diseases, and protect against cancers.…”
Section: Introductionmentioning
confidence: 99%
“…21 Chondrocyte apoptosis is generally considered a vital pathological feature of OA. 23 LIG can protect C2C12 cells from TNF-α-induced apoptosis during differentiation by inhibiting apoptosis and inducing cell proliferation. LIG, a quinone extracted from the roots of Plumbago plants, has been applied widely to treat various diseases because of its anti-apoptotic property.…”
Section: Discussionmentioning
confidence: 98%
“…22 LIG can inhibit the hypertrophy of cardiomyocytes stimulated by Ang II, which may be attributed to the ability of LIG to suppress cardiomyocyte apoptosis. 23 LIG can protect C2C12 cells from TNF-α-induced apoptosis during differentiation by inhibiting apoptosis and inducing cell proliferation. 24 Given its anti-apoptotic effect on neurons, LIG can be developed as an effective drug for the prevention of vascular dementia.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have shown that LIG can inhibit the proliferation and migration of A7r5 cells induced by angiotensin-II (Ang-II), and also has anti-thrombotic and anti-platelet aggregation effects, and improves the aggregation state of red blood cells (Lu et al, 2006(Lu et al, , 2014. Recent studies show that LIG exerted protective effects on excessive migration and migration in vascular smooth muscle cells (VSMCs), which was related to the c-Myc/MMP2 signaling pathway (Chung et al, 2012;Luo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%